2008
DOI: 10.1111/j.1478-3231.2008.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe prevents cholesterol gallstone formation in mice

Abstract: In a murine model of GSD, EZET prevented gallstone formation by reducing intestinal cholesterol absorption and increasing bile salt-dependent and -independent bile flow. EZET could be useful in preventing GSD disease in susceptible patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 50 publications
(74 reference statements)
4
30
0
Order By: Relevance
“…Ezetimibe has not been shown to increase the risk of gall stones perhaps because the drug has its primary effect in reducing cholesterol absorption. Indeed in the golden Syrian hamster Ezetimibe reduced diet-induced increase in biliary cholesterol [99], and, in gallstone-susceptible mice fed lithogenic diets, Ezetimibe prevented gall stone formation [100]. Inhibition of NPC1L1 by Ezetimibe is associated with an improvement in hepatic steatosis.…”
Section: Gene Regulation Of Chylomicron Metabolismmentioning
confidence: 99%
“…Ezetimibe has not been shown to increase the risk of gall stones perhaps because the drug has its primary effect in reducing cholesterol absorption. Indeed in the golden Syrian hamster Ezetimibe reduced diet-induced increase in biliary cholesterol [99], and, in gallstone-susceptible mice fed lithogenic diets, Ezetimibe prevented gall stone formation [100]. Inhibition of NPC1L1 by Ezetimibe is associated with an improvement in hepatic steatosis.…”
Section: Gene Regulation Of Chylomicron Metabolismmentioning
confidence: 99%
“…It is also found that high doses of estrogen augment intestinal cholesterol absorption [102], contributable in part to an up-regulated expression of intestinal sterol influx transporter Niemann-Pick C1 like 1 protein (NPC1L1) via the intestinal ESR1 pathway [115]. Because of species differences, NPC1L1 is expressed in the livers of humans and hamsters [116,117,118], but not in mouse livers [117,119,120]. Together with hepatic lipid transporters such as ABCG5/G8 on cholesterol secretion, ABCB11 on bile salt secretion and ABCB4 on phospholipid secretion [1], NPC1L1 may participate in the regulation of biliary cholesterol secretion.…”
Section: Molecular Mechanisms Underlying the Effect Of Estrogen On Gamentioning
confidence: 99%
“…This may result from decreased hepatic cholesterol biosynthesis and consequently reduced cholesterol concentrations in bile. Further mouse models [101,102] found ezetimibe to exert its protective effect through the reduced absorption of intestinal cholesterol coupled with an increased bile flow. This is an exciting area of research that holds preventative potential in high-risk groups.…”
Section: Environmental Factorsmentioning
confidence: 99%